Kinetic Studies on Thermal Decomposition of Oxalates Doped with Malonate - Suryanarayanan, M.P. (Asian Journal of Chemistry, 2016)
Thermal decomposition of metal oxalates is one of the important methods of preparation of pure or mixed metal oxides having special properties. Cationic or anionic doping may affect their decomposition. Here, the effect of doping by malonate ion on the thermal decomposition of oxalates of lead, zinc, manganese, nickel and cobalt was studied. The pure oxalates were prepared by treating a hot solution of salt of the metal with a hot solution of sodium oxalate. The doped samples of the above oxalates were prepared by taking a mixture of sodium oxalate and sodium malonate for precipitation. The decomposition was followed by thermogravimetric method The kinetic parameters like energy of activation (E), frequency factor (Z) and entropy of activation (ΔS*) of cobalt oxalate and nickel oxalate decreased considerably whereas the values for oxalates of lead, zinc and manganese increased on doping. The temperature at which the decomposition began (Ti) and temperature of completion (Tf) decreased whereas temperature of maximum decomposition (Ts) increased for cobalt oxalate and remained constant for nickel oxalate. In the case of lead oxalate doping with malonate ion increased Ti, but no appreciable change was observed for Tf and Ts. For zinc oxalate and manganese oxalate Ti, Tf and Ts remained practically constant.